The "Awal Mula Peh Cun di Tangerang": An Animated Film about Acculturation of Chinese Culture Fort in Tangerang - Dewi Isma Aryani; Krisanti Fransissca Ribenty Setiawan; I Nyoman Natanael (Journal of Games, Game Art, and Gamification, 2021)
The Peh Cun tradition is an Indonesian tradition that is acculturated with Chinese culture. The celebration of the Peh Cun tradition in Tangerang City is one of the oldest Peh Cun celebrations in Indonesia. In the celebration of Peh Cun there are many activities carried out such as: prayer, dragon boat race, eating Bacang, and also the people's market. The purpose of this design is to participate in preserving and introducing the Peh Cun tradition of the Chinese Benteng community in Tangerang to the Indonesian people with an age range of 7-20 years through the medium of short animated films. The benefits of this design are expected to increase public knowledge about one of the acculturation cultures that exist in Indonesia so that this culture remains sustainable. The design of the short animated film is carried out in a two-dimensional style suitable for cartoon type films so that it can be enjoyed by various ages, and the distribution of this short film is carried out through social media such as Instagram and Youtube as an educational function.